VD_FINDINFO Jug / 2015 / 455 vom 3. August 2015 - VD Tribunal cantonal (2015)
TRAVAIL D'INTÉRÊT GÉNÉRAL, ADMISSION DE LA DEMANDE, VIOLATION D'UNE OBLIGATION D'ENTRETIEN | 217 CP, 37 al. 1 CP, 42 al. 1 CP